FOOD AND FEEDING HABITS OF THE DEMERSAL FISHES OFF BOMBAY - Suseelan, C; Nair, K V Somasekharan (Indian Journal of Fisheries, 2011)
The food and feeding habits of some of the common fishes landed by the trawlers at Bombay have been studied by employing the points method and the volumetric method. Ilisfia filigera has been observed to be carnivorous, feeding chiefly on Acetes and teleosts, and Thrissocles malabarica feeds predominantly on planktonic organisms. The food of the catflshes consisted of benthic epifauna and infauna and also fishes. Polydactylus indicus and Polynemus heptadactylus were feed ing at all depths in the water column. Pomadasys hasta was noted to be mostly a benthic feeder. Pseudosciaena diacanthus, Otolithoides brunneus, Otolithus ruber, Johnius dussumieri, J. carutta, J. axillaris, J. aneus and Sciaena dussumieri fed chiefly on prawns, Acetes and fishes. Muraenesox talabonoides has been found to be predacious mainly on fishes. The seasonal variation in the diet of the fishes as a whole was determined by finding out the ’food index’. Prawns and teleosts were the most important food items consumed by the majority of the species. The values of the ’feeding index’ did not show any significant variations in the different months. However, it was slightly higher during the period July to September.